The psychology of humor : a reference guide and annotated bibliography - Roeckelein, Jon E. (Greenwood Press, 2002)
This work traces the origins and evolution of the concept of humor in psychology from ancient to modern times with an emphasis on an experimental/empirical approach to the understanding of humor and sense of humor. In addition to more than 3,000 important citations and references pertaining to the history, theories, and definitions of the concept of humor, this reference guide contains more than 380 recent (post-1970) annotated entries on the psychology of humor in its bibliographic section. The book describes various psychological, nonpsychological, and philosophical theories and definitions of humor, and focuses on the methodological concerns of psychologists regarding the scientific investigation of humor. The bibliography is organized under 10 categories, including Bibliographies and Literature Reviews of Humor, Cognition and Humor, Methodology and Measurement of Humor, and Social Aspects of Humor.